Developing interactive storytelling-based learning video to enhance students' numerical literacy in geometry - Susanti, Vica Amalia; Nurhasanah, Farida; Chrisnawati, Henny Ekana (Universitas Ahmad Dahlan, 2024)
Literacy is the ability to understand, use, and interpret written information. One of the fundamental forms of literacy that is embedded in everyday life is numerical literacy, which refers to an individual's ability to apply numerical and arithmetic concepts in daily life and interpret quantitative information in their surroundings. This research aims to develop a valid, practical, and effective interactive storytelling-based learning video to enhance students' numerical literacy in geometry. To this end, Plomp’s research and development method was applied. The result showed that, firstly, the developed product was valid, with an average total validity score of 0.910 for content validation and 0.860 for media validation. Secondly, the product was deemed practical, with an average score of 91.67% based on teacher evaluation and 80.31% based on student evaluation. Thirdly, the product was considered effective in improving students' numerical literacy, with calculated values t obs = 11.5084 and critical region = t, t>1.721, as well as an average N-Gain score of 0.668, indicating a moderate level of improvement. These results indicate that the developed interactive storytelling-based learning video is valid, practical, and effective in enhancing students' numerical literacy in geometry.